2015
DOI: 10.1007/s40474-015-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Executive Difficulties in Developmental Coordination Disorder: Methodological Issues and Future Directions

Abstract: Motor skills and cognition have often been studied separately, but there is increasing understanding of the close relationship between these abilities over development. Motor coordination difficulties are central to the diagnosis of Developmental Coordination Disorder (DCD), and recent evidence suggests that certain cognitive processes, known as 'executive functions', may be affected in individuals with this neurodevelopmental disorder. In this article, we review the research concerning executive functions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 63 publications
2
35
0
5
Order By: Relevance
“…Children with DCD performed worse than TD children in all inhibitory control tasks (Go‐No‐Go App and Hayling Part B tests), similar to previous studies (Leonard & Hill, ; Mandich, Buckolz, & Polatajko, , ; Michel, Roethlisberger, Neuenschwander, & Roebers, ; Querne et al, ). The singular contribution of the present study showed that the differences between the DCD and TD groups occurred in the inhibition tasks with motor and also with verbal responses.…”
Section: Discussionsupporting
confidence: 89%
“…Children with DCD performed worse than TD children in all inhibitory control tasks (Go‐No‐Go App and Hayling Part B tests), similar to previous studies (Leonard & Hill, ; Mandich, Buckolz, & Polatajko, , ; Michel, Roethlisberger, Neuenschwander, & Roebers, ; Querne et al, ). The singular contribution of the present study showed that the differences between the DCD and TD groups occurred in the inhibition tasks with motor and also with verbal responses.…”
Section: Discussionsupporting
confidence: 89%
“…Third, our study focused on standardized and experimental measures of executive function, in which task demands were set by the experimenter and did not necessarily represent the demands of executive function tasks in everyday life. More ecologically valid measures of executive function assessing real‐life situations and ‘hot’ executive functions, including emotional and motivational aspects, might further contribute to understanding executive function difficulties associated with poor motor skills …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified executive function deficits in children with DCD or those with motor difficulties (children with poor motor skills but no diagnosis; see Wilson et al and Leonard and Hill for recent reviews). However, this research is largely cross‐sectional.…”
mentioning
confidence: 99%
“…ASD and ADHD have been linked with executive function difficulties and it is possible that the working memory difficulties identified in our DCD sample may be due to this. Certainly a recent review identified that children with DCD present with wide-ranging executive difficulties (Leonard & Hill, 2015). Similarly, attention problems have been reported in children with DCD (Dewey et al, 2002;Querne et al, 2008) and poor attention may influence working memory performance, as the ability to selectively process/attend to relevant information will inevitably influence how information is retained in working memory.…”
Section: Discussionmentioning
confidence: 99%